PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA TRANSFER, DAN BELANJA MODAL TERHADAP LAJU PERTUMBUHAN EKONOMI DI PROVINSI NUSA TENGGARA BARAT TAHUN 2015–2024 : The Influence Of Regional Original Revenue (PAD), Transfer Funds, And Capital Expenditure On Economic Growth Rate In West Nusa Tenggara Province For The Period 2015–2024 - Nurmala, Baiq; Harsono, Iwan; Sutanto, Himawan; Astuti, Endang; Yuniarti, Titi (Ganec Swara, 2025)
This study aims to assess the impact of Locally-Generated Revenue (PAD), Central Government Transfers (DTB), and Capital Expenditure (BM) on the dynamics of economic growth in West Nusa Tenggara Province over the period 2015 to 2024. The analysis adopts a quantitative approach using multiple linear regression on annual secondary data, supported by classical assumption tests to ensure the validity of the estimation model. The results indicate that, collectively, the three independent variables significantly influence regional economic growth, as reflected by an F-statistic value of 15.47 (p<0.05) and a coefficient of determination (R²) of 0.82828. However, partial testing reveals that only DTB has a statistically significant effect, with a negative relationship, while PAD and BM are not individually significant. These findings highlight the need to enhance the efficiency of intergovernmental transfer management and to optimize strategies for improving local revenue generation and allocating capital expenditures productively, in order to support sustainable regional economic development